Implementing an IBM high-performance computing solution on IBM POWER8 - Quintero, Dino (IBM redbooks., 2015)
This IBM® Redbooks® publication documents and addresses topics to provide step-by-step programming concepts to tune the applications to use IBM POWER8® hardware architecture with the technical computing software stack. This publication explores, tests, and documents how to implement an IBM high-performance computing (HPC) solution on POWER8 by using IBM technical innovations to help solve challenging scientific, technical, and business problems. This book demonstrates and documents that the combination of IBM HPC hardware and software solutions delivers significant value to technical computing clients in need of cost-effective, highly scalable, and robust solutions. This book targets technical professionals (consultants, technical support staff, IT Architects, and IT Specialists) who are responsible for delivering cost-effective HPC solutions that help uncover insights among clients' data so that they can act to optimize business results, product development, and scientific discoveries.